A biodegradable and rechargeable fiber battery. Issue 16 (20th April 2021) - Mei, Tenglong; Wang, Chuang; Liao, Meng; Li, Jiaxin; Wang, Liyuan; Tang, Chengqiang; Sun, Xuemei; Wang, Bingjie; Peng, Huisheng
Abstract : A biodegradable and rechargeable fiber battery was made by designing biodegradable fiber electrodes and a chitosan separator with body fluid as electrolyte. It shows decent power capability in vivo . After use, it is biodegraded with high safety. Abstract : It is critical to realize biodegradable and rechargeable batteries that are also flexible and safe for power supplies in vivo, yet they remain unavailable. Here, we discovered such a biocompatible battery by designing biodegradable fiber conductors incorporated with polydopamine/polypyrrole composite material as the anode and MnO2 as the cathode, biodegradable chitosan as the separator and body fluid as the electrolyte. It can be directly injected into the body mini-invasively and well integrate with biological tissues without inducing immune responses. It delivered a specific capacity of 25.6 mA h g −1 with a retention of 69.1% after 200 charge/discharge cycles to power various biomedical devices. For instance, it was demonstrated to effectively power biosensors in the body. After completing the mission, it could be biodegraded, eliminating the need of surgery to remove it.